Manipulative Movement Learning During the COVID-19 Pandemic: An Approach to Implementing Online-Based Physical Education Learning - Firmana, Iif; Subarjah, Herman; Mahendra, Agus; Nuryadi, Nuryadi; Sofyan, Davi (Department of Physical Education, Sport, Health and Recreation, 2023)
The purpose of this study is to see how using online learning improves learning outcomes through manipulative movements. The method used in this research is class action research. The subjects involved in this study were 30 students, consisting of 18 male students and 12 female students. This study was divided into two cycles, each of which included two actions. Data collection techniques in this study included observation and tests of manipulative learning outcomes. The results of this study indicate that the application of online learning has an influence on increasing learning outcomes through manipulative movements. This can be seen from the observational data on the learning outcomes of manipulative movements; the category is less if it is presented at 65.64%. After being given treatment, the learning outcomes of students' manipulative movements were in the sufficient category if the percentage was 71.28%. This research concludes that online learning is an alternative to improving the learning outcomes of manipulative movements during the COVID-19 pandemic.